Efficacy of pressure parameters obtained during contrast medium-induced submaximal hyperemia in the functional assessment of intermediate coronary stenosis. (1st January 2016) - Kanaji, Yoshihisa; Murai, Tadashi; Lee, Tetsumin; Matsuda, Junji; Usui, Eisuke; Araki, Makoto; Niida, Takayuki; Sadamitsu, Ichijo; Rikuta, Hamaya; Yonetsu, Taishi; Kimura, Shigeki; Kakuta, Tsunekazu
Abstract: Background: Despite evidence demonstrating the superiority of percutaneous coronary intervention guided by fractional flow reserve (FFR), FFR evaluation has not been widely adopted. We sought to determine the diagnostic performance of baseline conditions and contrast medium-induced pressure indices in predicting FFR. We hypothesized that the contrast medium-induced end-diastolic pressure parameter would offer superior diagnostic agreement with FFR, compared to other indices. Methods & results: Ninety-one intermediate stenoses in 75 patients were studied prospectively. The baseline distal coronary pressure to aortic pressure ratio (Pd/Pa) and end-diastolic instantaneous Pd/Pa 60 ms before the electrocardiographic R-wave (ED-Pd/Pa) were measured; then, after intracoronary injection of 6 mL contrast medium at 3 mL/s, Pd/Pa (C-Pd/Pa) and end-diastolic Pd/Pa (C-ED-Pd/Pa) were obtained. Subsequently, conventional FFR was measured as a reference standard. Of the 91 lesions, 11 (12.1%) were excluded because of suboptimal data acquisition, leaving 80 for final analysis. C-ED-Pd/Pa values (median 0.80 [interquartile range 0.70–0.88]) were significantly lower than conventional FFR (0.83 [0.75–0.89], P < 0.01), whereas Pd/Pa (0.93 [0.90–0.96], P < 0.01), ED-Pd/Pa (0.91 [0.87–0.93], P < 0.01), and C-Pd/Pa (0.85 [0.79–0.90], P < 0.05) were significantly higher. Correlation coefficients (R) with conventional FFR were 0.74 (standard error of the estimate [SEE] 0.067, P < 0.0001), 0.78 (SEE 0.062, P < 0.0001), 0.85 (SEE 0.052, P < 0.0001), and 0.93 (SEE 0.037, P < 0.0001) for Pd/Pa, ED-Pd/Pa, C-Pd/Pa, and C-ED-Pd/Pa, respectively. Diagnostic accuracy was 81.2%, 83.8%, 87.5% and 93.8% for Pd/Pa, ED-Pd/Pa, C-Pd/Pa, and C-ED-Pd/Pa, respectively. Conclusions: Among baseline indices and contrast-induced pressure parameters, C-ED-Pd/Pa is a novel, feasible, and high-performance measure for the physiological assessment of intermediate coronary stenosis.